Lament in Jewish Thought Philosophical, Theological, and Literary Perspectives - Ferber, Ilit; Schwebel, Paula (Perspectives on Jewish Texts and Contexts, 2014)
This collection features essays by leading scholars on the philosophical, theological, poetic and cultural aspects of lament, touching on the textual traditions of lament in Judaism, from Biblical, rabbinic and medieval iterations to contemporary Yemenite oral lamentations. The volume also includes four texts on lament by Gershom Scholem, translated here for the first time into English, as well as essays interpreting Scholem`s challenging work.